EMOTIONAL MANAGEMENT OF TEAMS IN A HOSPITAL ENVIRONMENT - José Barbas Pinto, Marco (Health and Society, 2024)
The paper addresses the importance of emotional management and teamwork in the organizational context of a hospital, highlighting that the effectiveness of a team depends on alignment with the organization’s objectives, collaboration between different hierarchical levels, and employee motivation. Leadership plays a crucial role, and the leader must be democratic and involved, promoting an environment of support and effective communication. In addition, the text emphasizes that interaction between team members generates synergies that enhance creativity, flexibility, and productivity. Maslow’s theory of human needs is mentioned, suggesting that satisfying basic needs is fundamental to employee motivation and self-realization. Finally, creating a team spirit and being results-oriented are essential for organizational success.